2010
DOI: 10.1099/mic.0.038232-0
|View full text |Cite
|
Sign up to set email alerts
|

Mixotrophic and photoheterotrophic metabolism in Cyanothece sp. ATCC 51142 under continuous light

Abstract: The unicellular diazotrophic cyanobacterium Cyanothece sp. ATCC 51142 (Cyanothece 51142) is able to grow aerobically under nitrogen-fixing conditions with alternating light-dark cycles or continuous illumination. This study investigated the effects of carbon and nitrogen sources on Cyanothece 51142 metabolism via 13 C-assisted metabolite analysis and biochemical measurements. Under continuous light (50 mmol photons m "2 s "1 ) and nitrogen-fixing conditions, we found that glycerol addition promoted aerobic bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
74
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 85 publications
(78 citation statements)
references
References 48 publications
3
74
1
Order By: Relevance
“…However, some of the strains (Tables I and II) showed significantly higher nitrogenase activity, suggesting that glycerol is being metabolized in the cells and can be used as a source of reductants. On a similar note, Feng et al (2010) showed that Cyanothece sp. ATCC 51142 could metabolize Glc, but this carbon source did not contribute to biomass production.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…However, some of the strains (Tables I and II) showed significantly higher nitrogenase activity, suggesting that glycerol is being metabolized in the cells and can be used as a source of reductants. On a similar note, Feng et al (2010) showed that Cyanothece sp. ATCC 51142 could metabolize Glc, but this carbon source did not contribute to biomass production.…”
Section: Discussionmentioning
confidence: 87%
“…Unlike Cyanothece sp. ATCC 51142, which utilizes glycerol for the production of biomass (Feng et al, 2010), the other Cyanothece spp. strains did not exhibit any significant difference in growth rate when grown in the presence of glycerol (data not shown).…”
mentioning
confidence: 99%
“…4b). In this context, we have recently shown that Cyanothece 51142 uses glycerol as the sole carbon source when cells are grown under photomixotrophic conditions in the presence of glycerol 25 .…”
Section: Resultsmentioning
confidence: 99%
“…As evidence accumulates, it seems that the ability of using DOM as an alternative source of nutrients under limiting situations is common in various planktonic groups (Stoecker et al, 2017). Among marine diazotrophs, unicellular cyanobacteria such as Cyanothece have been reported to grow on glycerol (Feng et al, 2010), and filamentous diazotrophs such as Trichodesmium may obtain as much carbon from amino acids assimilation as from CO 2 fixation in the field . Non-cyanobacterial and nonphotosynthetic diazotrophs require external sources of DOM as energy sources (Riemann et al, 2010).…”
Section: Introductionmentioning
confidence: 99%